Effectiveness of Written vs. Oral Corrective Feedback in Syntactic Structure Mastery - Ramadhan, Fatih Humam (Sekolah Tinggi Agama Islam Kuningan, 2025)
This study explores the effectiveness of written and oral corrective feedback in improving mastery of syntactic structures. The background of the study emphasizes the need for correction strategies capable of helping students understand and apply grammar accurately. Qualitative methods were used through observations, interviews, and document analysis to analyze students' responses to both types of feedback. Results show that written feedback provides a permanent reference that can be reviewed repeatedly, while oral feedback encourages instant correction and interactive discussion. The implication is that teachers should combine the two methods so that students get a combination of detailed explanations and immediate corrections, while considering students' motivation and comfort factors in receiving corrections.